EFEK ROLE PLAY TERHADAP KEMAMPUAN BERBICARA SISWA KELAS 1 SMP N 14 PEKANBARU - Soraya Fitri Soraya Fitri; Marzuki Marzuki '; Mahdum Mahdum ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Role play is one of teaching techniques that can be used to familiarize students to use the language orally. It provides more oportunities for the students to use the language orally and build interaction with each other. This study was a pre- experimental research. This research was aimed to find out the effect of role play on the speaking ability of the first year students of SMP N 14 Pekanbaru. This reasearch was conducted toward the first year students of SMP N 14 Pekanbaru from May to June 2015. The subject of this research was class VII.7 which consisted of 32 students. The data was collected by giving a pre-test and a post-test to students in the form of picture descripyion. The data was assesed by the three raters and analyzed by using SPSS 20. The result of the reserch showed the interval score in the pre-test and the post-test was 10.49 where the score of the pre-test was 50 and the score of the post test increased to 60.38. Therefore, it can be concluded that role play gives positive effects to the students’ speaking ability.Keywords:Role Play, Speaking Ability